Search for new phenomena in events with three charged leptons at √s=7 TeV with the ATLAS detector - Alonso, Francisco (2013)
A generic search for anomalous production of events with at least three charged leptons is presented. The search uses a pp-collision data sample at a center-of-mass energy of √s=7 TeV corresponding to 4.6 fb-1 of integrated luminosity collected in 2011 by the ATLAS detector at the CERN Large Hadron Collider. Events are required to contain at least two electrons or muons, while the third lepton may either be an additional electron or muon, or a hadronically decaying tau lepton. Events are categorized by the presence or absence of a reconstructed tau-lepton or Z-boson candidate decaying to leptons. No significant excess above backgrounds expected from Standard Model processes is observed. Results are presented as upper limits on event yields from non-Standard-Model processes producing at least three prompt, isolated leptons, given as functions of lower bounds on several kinematic variables. Fiducial efficiencies for model testing are also provided. The use of the results is illustrated by setting upper limits on the production of doubly charged Higgs bosons decaying to same-sign lepton pairs.